(untitled) (Khairulummah, 2024)
Today for hen sacrificing we have a big tool, which proceeds with scarifying and production of all processes, from one side they put the hen and on the other side the pure canned meat is out, the whole process of the scarifying and pealing is done here. All these processes are done via electronic tools, these tools are much sharper, and are installed between two walls, they have many parts, where many hens are being hanged from their feet. Today all the Islamic markets are indeed filled with canned meat, which are the production of America, England, Scotland Australia, and Brazil. Meanwhile, bulls and sheep are firstly shaved via gas, and later on sacrificed, or they are shut by a bullet on their head and later on sacrificed, they can die before the sacrifice. This is a very crucial issue because all the Islamic markets are filled with such canned meat, where Muslims are unaware that this canned meat is foreign or domestic production, and at the same time people do not understand its verdict as well. My aim from this study is to make sure of the verdict of such canned meat, and let my people know regarding its lawfulness and unlawfulness. I have conducted this study library-based, I have utilized pertinent books and scholars’ views and have my views as well. Finlay, I have come to the result that; Muslims should avoid using such canned meat because their sacrifice has problems, if it’s not forbidden, but has hesitation, Muslims must try their best not to use canned meat.